2019
DOI: 10.1002/suco.201800137
|View full text |Cite
|
Sign up to set email alerts
|

Shear strengthening of reinforced concrete beams using prefabricated ultra‐high performance fiber reinforced concrete plates: Experimental and numerical investigation

Abstract: This paper presents the efficiency of using prefabricated ultra‐high performance fiber reinforced concrete (UHPFRC) plates in shear strengthening of reinforced concrete (RC) beams experimentally and numerically using finite element method. In order to ensure high quality and facilitate the strengthening process on site applications, it has been considered to apply UHPFRC as a plate pasted on concrete surface using epoxy. Tested specimens included four strengthened beams besides three control beams. Strengtheni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…In addition, the authors numerically investigated the tested beams and considered nonlinear FEM software of ABAQUS. It was reported by the numerical study that a good agreement between experimental and FEM results was detected, and it was documented that FEM is able to obtain the best-fitted shear behaviors (load-deflection curve, peak load, cracking pattern) of the RC beams [49].…”
Section: Shear Behaviorsmentioning
confidence: 76%
“…In addition, the authors numerically investigated the tested beams and considered nonlinear FEM software of ABAQUS. It was reported by the numerical study that a good agreement between experimental and FEM results was detected, and it was documented that FEM is able to obtain the best-fitted shear behaviors (load-deflection curve, peak load, cracking pattern) of the RC beams [49].…”
Section: Shear Behaviorsmentioning
confidence: 76%
“…(ii) Tensile damage parameter (d t ): e reinforcement steel was modelled using elastic-perfectly plastic material, as suggested in [23]. e relationship between the reinforcement steel and concrete was modelled as a perfect bond (embedded region, whereas the concrete was the host element).…”
Section: Methodsmentioning
confidence: 99%
“…Shear failure is unfavourable for engineers because of its sudden occurrence with a brittle failure mode, and many studies have focused on improving the capacity and ductility of RC beams strengthened in shear with UHPFRC [13,[18][19][20][21][22]. Sakr et al [23] proposed a 3D finite element model (FEM) to investigate the behaviour of RC beams strengthened in shear with prefabricated UHPFRC plates by using (a) one longitudinal vertical-side strengthening and (b) two longitudinal vertical-side strengthening. ey concluded that the prefabricated UHPFRC plates could significantly enhance the ultimate load carrying capacity, ductility, and strain of longitudinal reinforcement in the strengthened RC beams compared with the control beam failed in shear.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, it can greatly reduce the weight of bridges and improve durability in bridge engineering [7,8]. It can also be used in restoration projects, such as repairing bridge deck defects [9,10], repairing bridge piers [11,12], repairing anticollision layers [13], dams [14], and repairing tunnels [15,16]. Nonetheless, whilst the early strength develops slowly under normal temperature curing conditions, UHPC needs a hightemperature curing condition to obtain ultrahigh performance and high early strength.…”
Section: Introductionmentioning
confidence: 99%